2014
DOI: 10.1016/j.virol.2014.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA initiates replication of yellow fever vaccine in vitro and elicits virus-specific immune response in mice

Abstract: Yellow fever (YF) causes an acute hemorrhagic fever disease in tropical Africa and Latin America. To develop a novel experimental YF vaccine, we applied iDNA infectious clone technology. The iDNA represents plasmid that encodes the full-length RNA genome of 17D vaccine downstream from a cytomegalovirus (CMV) promoter. The vaccine was designed to transcribe the full-length viral RNA and to launch 17D vaccine virus in vitro and in vivo. Transfection with 10ng of iDNA plasmid was sufficient to start replication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 47 publications
(80 reference statements)
5
42
0
5
Order By: Relevance
“…Transfection was carried out essentially as described previously for plasmid encoding the full-length RNA viruses (Tretyakova et al, 2013; Tretyakova et al, 2014b). Replication of JEV and expression of JEV antigens in the transfected Vero cells were determined by the infectious center assay (ICA), indirect immunofluorescence assay (IFA) and western blot.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Transfection was carried out essentially as described previously for plasmid encoding the full-length RNA viruses (Tretyakova et al, 2013; Tretyakova et al, 2014b). Replication of JEV and expression of JEV antigens in the transfected Vero cells were determined by the infectious center assay (ICA), indirect immunofluorescence assay (IFA) and western blot.…”
Section: Methodsmentioning
confidence: 99%
“…At 48 h posttransfection, cells were rinsed with PBS, dried and fixed with cold acetone, then IFA was carried out using JEV (Nakayama strain) specific mouse antiserum VR-1259AF (ATCC), followed by the secondary fluorescein-labeled antibody to mouse IgG (H+L) (KPL, Gaithersburg, MD) as described previously (Pushko et al, 2001; Tretyakova et al, 2014b). Mounting medium containing propidium iodide counterstain (Vector Labs, Burlingame, CA) was used to visualize nuclei of the cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the formal resemblance of iDNA to DNA vaccines, the principal difference between them is the ability of iDNA to establish a productive infection (hence the term) upon transfection or after inoculation. Earlier it has been shown that vaccination with DNA encoding replicative-competent flavivirus genomes or genome segments (replicons) (Hall et al, 2003;Seregin et al, 2006;Tretyakova et al, 2014) even at submicrogram doses induces much stronger immune responses in mice as compared to "standard" DNA vaccines encoding non-replicating gene cassettes. An increased immunogenicity of iDNA vaccines in primates is yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%